2007
DOI: 10.1055/s-2007-966640
|View full text |Cite
|
Sign up to set email alerts
|

Prospective multicenter trial of capsule endoscopy in patients with chronic abdominal pain, diarrhea and other signs and symptoms (CEDAP-Plus Study)

Abstract: Strict patient selection on the basis of additional symptoms or signs is the key to increasing the yield of capsule endoscopy in patients with chronic abdominal pain. Inflammation seemed to be the additional sign with the highest value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
0
10

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 6 publications
3
47
0
10
Order By: Relevance
“…These include biochemical markers of inflammation such as raised C-reactive protein (CRP) or erythrocyte sedimentation rate (ESR) [174], thrombocytosis [175], anaemia, faecal markers of inflammation (e. g., calprotectin, lactoferrin), and symptoms of abdominal pain, diarrhoea [176], or weight loss [177]. Recurrent abdominal pain without other findings exceptionally rarely results in detection of clinically relevant lesions in the small bowel [178,179], little different from colonoscopy for isolated abdominal pain. This simply reflects the fact that endoscopy (of any sort) examines the mucosal lining and not the wall of the intestine, wherein lie the enteric nerves.…”
Section: Management Of Complications 731 Capsule Retentionmentioning
confidence: 99%
“…These include biochemical markers of inflammation such as raised C-reactive protein (CRP) or erythrocyte sedimentation rate (ESR) [174], thrombocytosis [175], anaemia, faecal markers of inflammation (e. g., calprotectin, lactoferrin), and symptoms of abdominal pain, diarrhoea [176], or weight loss [177]. Recurrent abdominal pain without other findings exceptionally rarely results in detection of clinically relevant lesions in the small bowel [178,179], little different from colonoscopy for isolated abdominal pain. This simply reflects the fact that endoscopy (of any sort) examines the mucosal lining and not the wall of the intestine, wherein lie the enteric nerves.…”
Section: Management Of Complications 731 Capsule Retentionmentioning
confidence: 99%
“…In adult patients, a previous study described 20 patients with chronic abdominal pain who were negative for extensive diagnostic workup, but no patients had clinically significant CE findings (Bardan, 2003). On the other hand, another study for adult patients demonstrated that abdominal pain with additional symptoms such as weight loss (>10% of body weight), inflammation shown by laboratory tests, chronic anemia, and suspected OGIB was associated with high diagnostic yield (May, 2007). In addition, another study applied to 16 patients with chronic abdominal pain without criteria for other gastrointestinal disorders and detected abnormal findings in 3 patients but in which only 1 patient, with additional symptom of weight loss, had relevant findings to abdominal pain in which ileal erosions and inflammation with a stricture which undetected by radiology (Spada, 2006).…”
Section: Abdominal Painmentioning
confidence: 99%
“…Although small bowel tumours have sometimes been identified in patients undergoing capsule endoscopy for unexplained abdominal pain [52] , two studies [75,76] evaluating a group of 36 patients with chronic abdominal pain of unknown origin and previous negative diagnostic work-up, found that capsule endoscopy was negative or not clinically relevant in more than 85% of subjects. On the other hand May et al [77] clearly demonstrated that when chronic abdominal pain is associated with other signs or symptoms (weight loss > 10% of body weight, inflammation shown by laboratory tests, chronic anemia, or suspected mid-gastrointestinal bleeding) relevant, or potentially relevant, findings are diagnosed by capsule endoscopy in about 60% of cases. C a p s u l e e n d o s c o p y h a s a l s o b e e n u s e d , w i t h promising results, in other rare clinical conditions such as indeterminate colitis [78,79] , small bowel transplantation [80] , graft versus host disease [81,82] , protein losing entheropathy [83] , primitive lymphangectasia [84] (mostly in the pediatric population), Whipple disease [85] and irritable bowel syndrome (with clinical suspicion of celiac disease) [86] .…”
Section: Other Indicationsmentioning
confidence: 99%